Embedded Linux Based Shopping Assistance System - Ayanabha Chakraborty; Prashant Konaje; Prabha Kasliwal (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
In a view to streamline shopping system and facilitate access to required commodities among innumerable varieties in a super market, personalized service can be exploited in automated manner through interactive graphical user interface. Implementation of location based several touch screen modules with a centralized database can provide easy, accurate and timely information in regards to query generated by the users. Availability of an item and its location with absolute identification are displayed on the screen to facilitate users to get access to it immediately. This not only saves valuable time and cumbersome manual procedure in finding desired products but also provides an easy-to-use interactive shopping experience without any effort. Personalized Shopping Assistance maintains a centralized database for all products in the super market with user-friendly graphical user interface touch screen modules at various locations.